Transmutation of central forces and Bertrand’s theorem - Carimalo Christian (Theoretical and Applied Mechanics, 2023)
The transmutation of central forces, or dual law, is a transformation linking potentials in power law relative to the distance, that is, those having a positive exponent to those having a negative exponent. A well known example is that of the Newtonian and Hookean potentials, which are also strongly linked by Bertrand’s famous theorem. This article shows how the use of dual law provides a better understanding of this theorem, and a new way to complete its demonstration